Efektivitas Kompres Hangat Dan Terapi Musik Terhadap Tingkat Nyeri Dismenore Remaja Di Masa Pandemi Covid-19 - Yuni Astuti; Tuti Anggarawati; Ida Sri Mulyani; Damayyanti Awwalina Ihza (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Dysmenorrhea is a medical condition that occurs during menstruation or menstruation, which can interfere with activities and requires treatment. Characterized by pain or tenderness in the abdomen or pelvis. The impact of dysmenorrhea is reduced concentration when studying, hampered sports activities and reduced time for social activities. With the increase in Covid-19 cases, people are becoming anxious if they have to come to health services for fear of contracting Covid-19. One action to reduce dysmenorrhea pain is using a warm compress combined with music therapy. This research is quantitative research using quasi-experimental research using a one-group pre-test-post-test design method and purposive sampling techniques. The location where the research will be conducted is STIKES Kesdam IV/Diponegoro with 30 respondents. The Numeric Rating Scale (NRS) is a tool used to evaluate dysmenorrhea pain. The Wilcoxon test was used to analyze research data. The results of this study show that giving a warm compress has an effect. with a combination of music therapy on the level of dysmenorrhea pain with a p value of 0.00 (<0.05).